Alternative Assessment in English Departments at Yemeni Universities: Attitudes and Practices of Faculty Members - Marwan Saeed Saif Moqbel; Abdu M. Talib Al-kadi (Taez University, 2020)
The study aimed to uncover faculty members' attitudes towards alternative assessment (AA) and substantiate the differences in their attitudes, if any, based on five variables: university, gender, specialization, experience, and academic rank. It also elucidates the extent this cohort of informants adopts AA in their teaching and ascertains the differences in their uses according to the same variables. The study involved collecting data, through a questionnaire, from a sample of (66) lecturers and professors of different ranks who teach EFL at the collegiate level in Yemen. The study took place in two public universities along with a private one. The results of descriptive statistics and inferential tests (t-test, Pearson correlation, ANOVA) revealed that the respondents were positive towards AA but this was hardly reflected in their teaching. Significant differences in their attitudes towards AA were attributable to gender but not to university, specialization, magnitude of experience, or academic rank. In terms of usage, significant differences pertained to the variable of university and not to gender, specialization, experience, or academic rank. The findings rationalized incorporating AAs in EFL programs to enhance seeding new models of assessment that results in efficient learning and teaching.